Neuroblastoma presenting as haemophagocytic lymphohistiocytosis - Pogorzala, Monika (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Haemophagocytic lymphohistiocytosis (HLH) is a rare, life-threatening syndrome of excessive activation of the immune system, which can be primary (genetically determined) or secondary (acquired). Secondary forms are most often triggered by infections, but also by autoimmune processes, neoplastic diseases, drugs, and metabolic diseases. Secondary HLH associated with malignancy occurs more often in adults, mainly in the course of lymphomas and leukaemia. It is rarely induced by solid tumours but can develop during chemotherapy. The presented case of a 1.5-year-old child reflects a very rare situation when symptoms of haemophagocytic syndrome turned out to be the primary manifestation of a non-haematological proliferative disease.